A Wireless Sensor Network Prototype System for Management of Wind and Solar Hybrid Energy Sources at The State Polytechnic of Malang - Wicaksono, Amartya Salsabiila Putri; Junus, Mochammad; Rasyid, Abdul; Adzikirani, Adzikirani (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Electrical energy plays a vital role in various aspects of life, including the education sector. At the State Polytechnic of Malang, electricity is primarily generated by coal burning, which poses environmental challenges. This study proposes a hybrid power generation system utilizing renewable energy sources, specifically wind and solar energy, with a battery as the storage medium. However, the unstable energy output from these sources can lead to overcharging. To address this issue, an energy management system was developed using a Wireless Sensor Network (WSN) integrated with a microcontroller to monitor and manage energy from both sources. The system comprises two nodes and one server. Each node includes a wind turbine, solar panel, sensors, relays, switches, a microcontroller, and wireless transmission devices to transmit data to the server, enabling real-time monitoring through a web-based interface. Test results demonstrate that the system effectively prevents overcharging, achieving a 100% success rate.